The Effectiveness Of Moringa oleifera L (Moringa oleifera L) Fraction On The Improvement Of Hemoglobine Levels Of Betinine Rat (Rattus norvegicus) Anemia Model Of Iron Deficiency - Ricika, Winda (Biomedical Journal of Indonesia, 2020)
The iron deficiency anemia is kind of anemia because the less of iron that make thefunction to tie oxygen is down. Young girl is one of sufferer group who’s prone to getanemia. The long consequence of anemia for the young girl will disturb fatal functionof some organ in their body. In general arise of headache symptoms and pain in thecentre of head. And the in pregnancy will increase some complication risk such asmaternal death. Premature born and perinatal death. One of nature ingredients(herbal) which is reported to have high iron content is kelor leaf (Moringa oleifera L) forabout 28, 29 mg/100 g kelor. The purpose of this research is to know the effectivenessof Kelor leave fraction ((Moringa oleifera L) to increase hemoglobin grade withpreclinical. Experimental research with complete random design (RAL) has been donein February till April 2019 in medical faculty laboratory of universitas sriwijayaPalembang. Sample of the research is female rat that has inclusion criteria as much30 rats. Divided into 5 group. That is negative control group. Positive control (ferrousfumarate 60%), n-heksan fraction, ethyl acetate, and 1% concentration of kelor leaveethanol, the data of Hb all of subject before and after treatment from subject of irondeficiency anemia has collected by using Easy Touch GCHb tool. The analysis data ofthis research used SPSS 2.2 version. The result of the research said that thehemoglobin grade before and after treatment showed significant increasing(p<0,05) forn – hexane fraction and acetate ethyl >45%. While ethanol fraction only 32%.